Selective nano alumina supported vanadium oxide catalysts for oxidative dehydrogenation of ethylbenzene to styrene using CO2 as soft oxidant - A.M. Elfadly; A.M. Badawi; F.Z. Yehia; Y.A. Mohamed; M.A. Betiha; A.M. Rabie (Egyptian Journal of Petroleum)
Nano alumina-supported V2O5 catalysts with different loadings have been tested for the dehydrogenation of ethylbenzene with CO2 as an oxidant. High surface area nano-alumina was prepared and used as support for V2O5 as the catalyst. The catalysts were synthesized by impregnation techniques followed by calcinations and microwave treatment, denoted as V2O5/γ-Al2O3-C and V2O5/γ-Al2O3-MW, respectively. The V2O5 loading was varied on nano-alumina from 5 to 30 wt%. The support and catalysts were characterized by X-ray diffraction (XRD), Barett–Joyner–Halenda (BJH) pore-size distribution, N2-adsorption isotherms, Fourier transform infrared (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and temperature programed desorption (TPD-NH3). The characterization results indicated that V2O5 is highly dispersed on alumina up to 30%-V2O5/γ-Al2O3-MW prepared by MW method. The TPD studies indicated that there are significant differences in acid amount and strength for V2O5/γ-Al2O3-C and V2O5/γ-Al2O3-MW-catalysts. The catalytic activity of the prepared catalysts was evaluated in the temperature range 450–600 °C in relation to the physicochemical properties and surface acidity. The results revealed that optimum catalytic activity and selectivity (∼100%) toward styrene production were obtained using 10% V2O5/γ-Al2O3-MW catalyst treated with microwave.